2015
DOI: 10.1111/jcmm.12606
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular features and therapeutic perspectives of spinal muscular atrophy with respiratory distress type 1

Abstract: Spinal muscular atrophy with respiratory distress (SMARD1) is an autosomal recessive neuromuscular disease caused by mutations in the IGHMBP2 gene, encoding the immunoglobulin μ-binding protein 2, leading to motor neuron degeneration. It is a rare and fatal disease with an early onset in infancy in the majority of the cases. The main clinical features are muscular atrophy and diaphragmatic palsy, which requires prompt and permanent supportive ventilation. The human disease is recapitulated in the neuromuscular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…In particular, some cases of CHN present with defects in respiration, swallowing and early death (17). Respiratory failure may be caused by central or peripheral mechanisms, such as impaired respiratory drive (18), or peripheral dysfunction or degeneration of NMJs (19). Recently, it was reported that Tr J heterozygote mice, similar to other animal models of CMT1, show axonal degeneration and denervated NMJs (20, 21).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, some cases of CHN present with defects in respiration, swallowing and early death (17). Respiratory failure may be caused by central or peripheral mechanisms, such as impaired respiratory drive (18), or peripheral dysfunction or degeneration of NMJs (19). Recently, it was reported that Tr J heterozygote mice, similar to other animal models of CMT1, show axonal degeneration and denervated NMJs (20, 21).…”
Section: Introductionmentioning
confidence: 99%
“…Future studies are needed to define novel treatment strategies. [20][21][22] In conclusion, spinal muscular atrophy with respiratory distress type 1 is an unusual type of SMA with respiratory failure and an ominous prognosis. It is of the utmost importance for pediatric intensivists to keep this life-threatening diagnosis in mind in infants dying with undetermined respiratory illness, weaning failure, or sudden death.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, he had a second homozygous variant c.861C>G, which has been reported with an allele frequency of 0.0033 in the South Asian population in the ExAC database. Since SMARD1 is recognized as an extremely rare disorder [16], the relatively high allele frequency of the c.861C>G variant indicates it is a non-pathogenic rare genetic variant. In any case, the c.861C>G is not expected to have an impact on IGHMBP2 in Patient 1, because the c.2T>C variant likely abolishes protein production.…”
Section: Discussionmentioning
confidence: 99%
“…Typically SMARD1 patients die within the first year of life due to respiratory failure [4,10,11]. However, the disease severity in SMARD1 may be variable, and juvenile onset of respiratory distress [12][13][14][15] with survival up to 20 years has been reported [14,16]. At the mild end of the IGHMBP2 mutation disease spectrum, patients present with CMT2S, a sensorimotor axonal polyneuropathy, usually with less pronounced neurophysiological changes compared to SMARD1, relatively spared respiratory function, and longer survival [1,15,17].…”
Section: Page 3 Of 18mentioning
confidence: 97%